EVALUATION OF PALIHAN JAVANESE CHRISTIAN CHURCH WORSHIP ROOM DESIGN TOWARDS NOISE HANDLING - Kartika Putri, Tabita Febriawaty; Setyowati, Erni (Border: Jurnal Arsitektur, 2023)
The construction of the New Yogyakarta International Airport required Palihan Javanese Christian Church to be relocated. Although it has been relocated, the new location of Palihan Javanese Christian Church remains very close to New Yogyakarta International Airport. The design of worship space at Palihan Javanese Christian Church then becomes a big challenge. Noise is one of the most challenging aspects for the success of the space design. Research on noise in the worship room of Palihan Javanese Christian Church was conducted to find out how much noise that enters the worship room of Palihan Javanese Christian Church and its causes, so that the design of the worship room of Palihan Javanese Christian Church can be evaluated to be better. The research was conducted by measuring noise in the worship room using a Sound Level Meter and by identifying the design of the worship room of Palihan Javanese Christian Church. From the research that has been done, noise that occurs in the worship room of Palihan Javanese Christian Church still exceeds the acceptable noise level for worship space.